Developing a Writing Workbook for Indonesian College Students of English - Ningrum, Ary Setya Budhi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The article presents the development of a writing workbook designed for the fourth semester students of a Writing III course at the English Education Program of State College for Islamic Studies (STAIN) Kediri. The Research and Development (R & D) project adopted the process-based writing approach consisting of eight steps: needs analysis, planning, first draft development, expert validation, product revision I, try-out, product revision II, and final product development. The results show that the process-based writing workbook can accommodate the learning needs of the target learners. The students found the clear writing stages that guide them through the whole process of writing, the well-designed exercises that integrated reading and writing activities, and the availability of good essays presented as models to be the strengths of the workbook.